Study of the structure of magnetic chambers and their relationship By giving me hysterics (Journal of the College of Basic Education, 2022)
Magnetic stones were studied using simple analysis and knowledge of the boundary conditions for the formation ofThese stones through studying the energy that is lost during the process of magnetization and explaining it, as well as studying the relationship of thesefields by the magnetic hysteresis curve and explain the hysteresis curve when an external magnetic field is applied to